2014
DOI: 10.1371/journal.pone.0111953
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Single Nucleotide Polymorphisms Associated with Acute Respiratory Distress Syndrome by Exome-Seq

Abstract: Acute respiratory distress syndrome (ARDS) is a lung condition characterized by impaired gas exchange with systemic release of inflammatory mediators, causing pulmonary inflammation, vascular leak and hypoxemia. Existing biomarkers have limited effectiveness as diagnostic and therapeutic targets. To identify disease-associating variants in ARDS patients, whole-exome sequencing was performed on 96 ARDS patients, detecting 1,382,399 SNPs. By comparing these exome data to those of the 1000 Genomes Project, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…Shortt et al 65 studied 96 patients with ARDS (70 Caucasian and 26 African Americans), and identified 76 novel ARDS susceptibility SNPs. They also selectively genotyped three of these SNPs, rs3848719 (ZNF335 gene that contributes in proliferation of neural progenitor cells and self-renewal), rs78142040 (ARSD gene that contributes to the development of cartilage and is a member of the sulfatase family), rs9605146 (in XKR3 gene that is a potential membrane transporter), in an additional 117 patients and found the correlation of rs3848719 and rs78142040 with APACHE II score quartile and 60-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Shortt et al 65 studied 96 patients with ARDS (70 Caucasian and 26 African Americans), and identified 76 novel ARDS susceptibility SNPs. They also selectively genotyped three of these SNPs, rs3848719 (ZNF335 gene that contributes in proliferation of neural progenitor cells and self-renewal), rs78142040 (ARSD gene that contributes to the development of cartilage and is a member of the sulfatase family), rs9605146 (in XKR3 gene that is a potential membrane transporter), in an additional 117 patients and found the correlation of rs3848719 and rs78142040 with APACHE II score quartile and 60-day mortality.…”
Section: Resultsmentioning
confidence: 99%
“…45 Sequencing of genomic coding regions (socalled exome sequencing) was done in a collaborative effort sponsored by the National Heart, Lung, and Blood Institute 46 and included 96 cases of ARDS. When ARDS cases were compared with presumably healthy controls in the 1000 Genomes Project, two SNPs in the genes XK related 3 and arylsulfatase D showed differential expression in ARDS cases, 31 We refer to candidate testing when an individual known entity (SNP, specific transcript, protein, etc) is quantified, whereas medium-throughput or high-throughput discovery approaches rely on known features but are capable of multiplex assays. For example, genome-wide association studies or cDNA microarrays rely on the knowledge of a genetic sequence to generate probes that will assay each SNP or transcript.…”
Section: Next-generation Sequencingmentioning
confidence: 99%
“…a common alternative name in parentheses if appropriate 26,27,[30][31][32]34,35 and proteins17,29,[36][37][38] are shown using Reference Sequence abbreviations, with common alternative names in parentheses.…”
mentioning
confidence: 99%
“…With an extremely high hospital mortality rate among 35-46% [2], current therapeutic strategies to increase ARDS survival consist of support to prevent ventilator induced lung injury, to improve oxygenation and gas exchange, advances in etiology and pathology of ARDS are urging. Clinical factors and protocolized therapeutic strategy poorly explain the outcome of ARDS, the role of genetic locus in the pathogenesis of ARDS is increasingly recognized [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%